ANALISIS NILAI TAMBAH DAN PENDAPATAN PENGOLAHAN PARE MENJADI KERIPIK PARE - Isabela Yulninsi; Dian Tariningsih; Nyoman Yudiarini; Diah Yuniti (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The main part of the bitter melon plant which has a high economic value is the fruit. This study aims to analyze the added value and income from processing bitter melon into bitter melon chips at UD Ratu Wiguna Desa Padangsambian, West Denpasar District, Denpasar City. Types of data in research includes qualitative data and quantitative data. Sources of data in this study are primary data and secondary data. The method of determining the respondent is carried out by the method of census. The results showed that the characteristics of the respondents included age, education and work experience. The added value of processing bitter melon into bitter melon chips at UD Ratu Wiguna in Padangsambian Village, West Denpasar District, Kota Denpasar, Rp. 31,750 per kilogram with a total production of 10 kilograms bitter gourd chips in one production process. Income received from proceeds processing bitter melon into bitter melon chips in one production process at UD Ratu Wiguna in Padangsambian Village, West Denpasar District, Denpasar City is Rp. 259,810. or Rp 5,196,200 per month.